The Influence of Mathematical Representation Ability and Spatial Ability on Students’ Mathematics Learning Outcomes in Terms of Gender - Nurma Izzati; Nurkhamdalah; Andini Rohmah; Faizah Firasyan; Nabila Zahrani; Ibnu Hazar Askalani; Pradini Hersafitri (MASI Mandiri Edukasi, 2025)
This quantitative experimental study aims to examine the effect of mathematical representation ability and mathematical spatial ability on students’ mathematics learning outcomes, with gender as a moderating factor. The population consisted of 74 third-semester Mathematics Education students at UIN Syekh Nurjati Cirebon during the 2024/2025 academic year. A sample of 30 students was selected using purposive sampling. Validated test instruments were used to measure mathematical representation ability, spatial ability, and learning outcomes. Data were analyzed using simple and multiple linear regression. The results show that for female students, both abilities significantly and positively influenced learning outcomes (p < 0.05). For male students, only mathematical spatial ability showed a significant effect (p < 0.05). These findings suggest that female students may be better at integrating representational and spatial skills in mathematical learning than their male counterparts